2014
DOI: 10.1136/bmjopen-2014-005005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mycophenolate mofetil on progression of interstitial fibrosis and tubular atrophy after kidney transplantation: a retrospective study

Abstract: ObjectivesChronic transplant dysfunction after kidney transplantation is a major reason of kidney graft loss and is caused by immunological and non-immunological factors. There is evidence that mycophenolate mofetil (MMF) may exert a positive effect on renal damage in addition to immunosuppression, by its direct antifibrotic properties. The aim of our study was to retrospectively investigate the role of MMF doses on progression of chronic allograft dysfunction and fibrosis and tubular atrophy (IF/TA).SettingRe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The immunosuppressive regimen given to patients at KAMC may have a role in this reduced rate. It is worth mentioning that in addition to MMF playing a major role in reducing DGF rates, there is evidence that it slows tubular atrophy progression and interstitial fibrosis [29], which are renal pathologies that significantly contribute to the development of ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive regimen given to patients at KAMC may have a role in this reduced rate. It is worth mentioning that in addition to MMF playing a major role in reducing DGF rates, there is evidence that it slows tubular atrophy progression and interstitial fibrosis [29], which are renal pathologies that significantly contribute to the development of ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Nakanishi and colleagues compared the antifibrotic effects of BMS-566419, a chemically synthesized IMPDH inhibitor, to MMF in the UUO rat model of renal fibrosis (Nakanishi et al, 2010). The results suggested that BMS-566419 and similar inhibitors have beneficial effects equivalent to MMF, and are potential therapeutic candidates for fibrotic renal disease (Mihovilovic et al, 2014; Morath et al, 2006; Nakanishi et al, 2010). Lastly, the active components of several traditional Chinese medicines with renal protective effects, such as celastrol, rhein, and danshensu, inhibit the NF-κB pathway (Guan et al, 2015; Kim et al, 2013).…”
Section: Intracellular Signaling Molecules Linked To Fibrosismentioning
confidence: 96%
“…''Are you anxious about your future?''). There are four different types of answers to the questions: dichotomous scale (23), multiple choice (9), open questions (6), and Likert scale (2).…”
Section: Lkd Questionnairementioning
confidence: 99%
“…Kidney transplantation has become a well-established method in the treatment of patients with end-stage renal failure and has led to an increased overall survival rate compared to patients on hemodialysis [1].The patient and graft survival have improved steadily due to better immunosuppressive regimens [2], improved surgical methods [3], and better anesthetic management [4].…”
Section: Introductionmentioning
confidence: 99%